Conceiving Socioscientific Issues in STEM Lessons from Science Education Research and Practice - Silvia Alcaraz-Dominguez; Mario Barajas (MDPI AG, 2021)
This paper aims to elicit the different conceptions of Socioscientific Issues (SSI) in formal, non-tertiary STEM lessons. An examination of recent publications in the field of science education was conducted to elicit the most common conceptions of SSI as per the components of STEM lessons, namely: purpose, contents, teaching and learning strategies and assessment. As for purpose, the conceptions elicited have been organized in terms of contributing to citizenship goals, or to scientific competence. As for contents, it was found that SSI are related both to knowledge of science and knowledge about science and linked to skills such as argumentation. In terms of teaching and learning strategies, SSI are mainly associated with Inquiry-Based Learning; and with student engagement techniques such as dilemmas and group discussions. Lastly, performance assessment of student learning processes and results is typical when SSI are conceived as a method of assessment of STEM lessons. This conception sets up strong foundations for the design and evaluation of innovative SSI teaching. It shall also help to open new lines of research establishing connections among applications of SSI in different subjects, cultural contexts and educational systems.